Learning Outcomes Development for Improving the Employment Rate of the Hotel Management Students at Guilin Tourism University in China - Jiarong Li; Nipaporn Khamcharoen (New Horizon of Education, 2025)
This study investigates the fluctuating employment rates of hotel management graduates from Guilin Tourism University, a Sino-foreign cooperative program with École hôtelière de Lausanne (EHL). Despite the program's aim to cultivate internationally competitive talent, employment rates have seen a significant decline, from a peak of 98.21% to a low of 45.28%. Through a mixed-methods approach—incorporating surveys of 246 graduates and 120 industry stakeholders, alongside focus group discussions—this research identifies critical deficiencies in graduates' professional knowledge, practical skills, and sense of responsibility. Concurrently, employers emphasized high expectations in professional ethics, service quality, adaptability, and English proficiency. Statistical analysis (e.g., correlation, regression) confirmed significant relationships between these competencies and employment outcomes.The findings reveal a pronounced gap between student competencies and industry demands. In response, this paper proposes an integrated set of strategies, including curriculum modernization, systematic practical training, soft skills development, enhanced career guidance, and faculty internationalization. These measures are designed to bridge the identified gap, improve graduate competitiveness, and ultimately contribute to the development of both the university and the regional tourism industry. The study offers valuable insights for optimizing Sino-foreign cooperative education models within China's evolving hospitality landscape.